2016
DOI: 10.1038/nm0216-217c
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Cardiac RKIP induces a beneficial β-adrenoceptor–dependent positive inotropy

Abstract: In the version of this article initially published, the labels to the left of the two micrographs in Figure 2c are reversed. Also, in Figure 4g, MKi67, used as a cell proliferation marker, is misspelled. The errors have been corrected in the HTML and PDF versions of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In addition, we discovered that the expression of phosphatidylethanolamine‐binding protein 1 (PEBP1) was influenced by exosomal miR‐4,507. Schmid et al reported that PEBP1 gene transfer in a mouse model of heart failure had beneficial effects since the modest overexpression of Raf kinase inhibitor protein, which regulates the expression of miR‐4,507, could produce a well‐tolerated, persistent increase in cardiac contractility . Finally, we predicted that exosomal miR‐3,656 would affect CSK, which is one of the critical negative regulators in the Src family of kinases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, we discovered that the expression of phosphatidylethanolamine‐binding protein 1 (PEBP1) was influenced by exosomal miR‐4,507. Schmid et al reported that PEBP1 gene transfer in a mouse model of heart failure had beneficial effects since the modest overexpression of Raf kinase inhibitor protein, which regulates the expression of miR‐4,507, could produce a well‐tolerated, persistent increase in cardiac contractility . Finally, we predicted that exosomal miR‐3,656 would affect CSK, which is one of the critical negative regulators in the Src family of kinases.…”
Section: Discussionmentioning
confidence: 85%
“…Schmid et al reported that PEBP1 gene transfer in a mouse model of heart failure had beneficial effects since the modest overexpression of Raf kinase inhibitor protein, which regulates the expression of miR-4,507, could produce a well-tolerated, persistent increase in cardiac contractility. 35 Finally, we predicted that exosomal miR-3,656 would affect CSK, which is one of the critical negative regulators in the Src family of kinases. The Src family of kinases regulates inflammation, cell proliferation, motility, and adhesion.…”
Section: Discussionmentioning
confidence: 98%